Manajemen Sekolah Lansia dalam Meningkatkan Kemandirian Peserta Didik Lanjut Usia di Sekolah Lansia Mutiara Senja Pekon Wates 2026 [Management of Elderly Schools in Improving the Independence of Elderly Learners at Mutiara Senja Elderly School Wates Village 2026] - Surya Dwi Saputra; Siswoyo Siswoyo; Arman Arman; Sofwan Adiputra (UKInstitute, 2026)
The implementation of education for older adults through elderly schools requires effective management so that the program can run well and produce a tangible impact. The application of such management can contribute to improving the independence of elderly learners within the school environment. This study aims to examine management functions, namely planning, organizing, implementation, and supervision, in the organization of learning activities for the elderly related to independence. This study employed a qualitative approach with a descriptive research design to provide an in-depth description of the implementation of elderly school management. The data collection techniques included observation, in-depth interviews, and documentation. The findings revealed that the management of Mutiara Senja Elderly School in Wates Village has been systematically implemented through the functions of planning, organizing, implementation, and supervision in a directed, participatory manner and oriented toward the needs of elderly learners. The implementation of this management has had a significantly positive impact on improving the independence of elderly learners, as indicated by increased self-confidence, social interaction skills, active participation, and independence in carrying out daily life activities. It is recommended that elderly schools continue to improve the quality of management functions through planning based on the needs of learners. Abstrak. Pelaksanaan pendidikan bagi lansia melalui sekolah lansia mensyaratkan manajemen yang efektif agar program dapat berjalan dengan baik dan berdampak nyata. Penerapan manajemen tersebut dapat berkontribusi terhadap peningkatan kemandirian peserta didik lanjut usia di lingkungan sekolah. Tujuan penelitian ini mencakup fungsi-fungsi manajemen yaitu perencanaan, pengorganisasian, pelaksanaan, dan pengawasan dalam penyelenggaraan kegiatan pembelajaran bagi lanjut usia terkait kemandirian. Metode penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif, untuk menggambarkan secara mendalam pelaksanaan manajemen sekolah lansia. Teknik pengumpulan data yang digunakan meliputi observasi, wawancara mendalam, dan dokumentasi. Hasil penelitian manajemen Sekolah Lansia Mutiara Senja Pekon Wates telah dilaksanakan secara sistematis melalui fungsi perencanaan, pengorganisasian, pelaksanaan, dan pengawasan yang terarah, partisipatif, serta berorientasi pada kebutuhan peserta didik lanjut usia. Penerapan manajemen tersebut memberikan dampak positif yang signifikan terhadap peningkatan kemandirian peserta didik lanjut usia, yang ditunjukkan melalui meningkatnya kepercayaan diri, kemampuan berinteraksi sosial, partisipasi aktif, serta kemandirian dalam menjalankan aktivitas kehidupan sehari-hari. Saran yang diajukan sekolah lansia diharapkan dapat terus meningkatkan kualitas fungsi manajemen melalui perencanaan yang berbasis kebutuhan peserta didik.